Analisis Kinerja Keuangan Perusahaan Dengan Menggunakan Metode Financial Analysis (Studi Kasus PT. Indika Energy Tbk Tahun 2014 – 2019) - Prasetyo, Wahyu Heri (Universitas Pendidikan Ganesha, 2021)
Financial analysis is a method that can be used to determine the financial performance of a company. The results of the analysis can be used by interested parties to make business decisions. So the purpose of this study is to find out about the financial performance of the company PT Indika Energy Tbk from the period 2014 to 2019. In this study, researchers used the Financial Ratio Analysis method. This type of research in this study uses a case study research type. To collect data, researchers used secondary data collection methods. The data is taken from the Indonesia Stock Exchange Website and Indika Energy's official website. The results showed that the company's financial condition was not good. The profitability ratio shows that for three years it has been minus. Even the company's debt is higher than the company's capital. The company's cash ratio also shows a number below 1, which means that the company's liquidity ratio is in an unsafe condition. In such conditions the company must be careful in managing debt.